Neighborhood resources and risk of cognitive decline among a community-dwelling long-term care population in the U.S. - Min Hee Kim; Ruth Dunkle; Philippa Clarke (Elsevier, 2023)
Objective: To examine the associations between neighborhood resources (i.e., number of restaurants, recreation centers, or social services for seniors and persons with disability per land area) and cognitive decline among a community-dwelling long-term care population and whether they differ by baseline cognition status. Study design: Prospective longitudinal cohort study. Methods: We used a longitudinal dataset that assessed over a two-year period older adults receiving state-funded home- and community-based services in Michigan Metropolitan areas (N = 9,802) and applied nonlinear mixed models with a random intercept with Poisson distribution. Results: Cognitively intact older adults were less likely to experience cognitive decline when they resided in resource-rich neighborhoods, compared to those cognitively intact but living in neighborhoods that lacked resources. But their cognitively impaired or dementia-diagnosed counterparts did not similarly benefit from living in neighborhoods with rich resources. Conclusions: Neighborhood resources may be an important aspect of intervention to mitigate cognitive decline before older adults become cognitively impaired.